Formação inicial e a efetivação da prática pedagógica de licenciado em pedagogia dos anos iniciais do ensino fundamental no município do Acará-Pará - VINAGRE, Marilia Souza (2021)
This present work entitled: “Initial training and pedagogical practice of the graduate in pedagogy of the early years of elementary school in the municipality of Acará-Pará” aims to understand the training and pedagogical practice of the licensed teacher in Pedagogy of the municipality of Acará, from two schools located in rural areas. In this sense, we seek to reflect on the process of the initial formation of pedagogues and the contribution of this formation to the knowledge built for the implementation of the pedagogical practice in service. The data obtained from the research had the contribution of two teachers from the early years, one from Paulo Freire School and the other from Rainbow School. The research is qualitative approach and descriptive-interpretative nature, developed through semi-structured interviews. The data bring results that allow us to understand that the initial formation of teachers who work in the early years of schools located in rural areas of the municipality of Acará, Pará, still leaves much to be desired in the implementation of pedagogical practice, considering that learning The practice and the appropriation of knowledge are only acquired in the daily life of the profession, because, according to the reports obtained, the teachers do not feel prepared only with the initial training to act as professionals in schools. For the teachers interviewed, the practice of pedagogical practice depends on knowledge acquired in the daily life of the profession and in continuing education.